Transformasi Follower to Leader pada Generasi Muda Bidang Bisnis dan Marketing - Febri Sari Siahaan; Amanda Sona Priscillia; Lesna Purnawan; Ayi Krisnha W.A.N; Ulfah Ulfah; Nuhfendi Nuhfendi; Caesar Rismanto; Dedianto Turnip; Rachman Hakim; Dadang Abdullah (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program was motivated by the low leadership mindset and leadership skills among young people in business and marketing, who tend to remain passive followers. The objective of this program was to enhance participants’ understanding, skills, and leadership attitudes through the from follower to leader approach. The methods applied included community education, science and technology diffusion, experiential learning-based training, mediation, and mentoring implemented through socialization, simulation, and follow-up assistance. The results showed a 37.6% increase in participants’ understanding based on pre-test and post-test scores, along with behavioral changes toward being more proactive, confident, and capable of making decisions. In addition, communication and teamwork skills improved significantly. This program demonstrates that experiential learning is effective in developing youth leadership. Therefore, this model is important to be further developed to enhance competitiveness in business and marketing.